2021
DOI: 10.1021/acsinfecdis.1c00424
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Antimicrobial Peptides Are Leading the Way to Combat Oropathogenic Infections

Abstract: Oral dental infections are one of the most common diseases affecting humans, with caries and periodontal disease having the highest incidence. Caries and periodontal disease arise from infections caused by oral bacterial pathogens. Current misuse and overuse of antibiotic treatments have led to the development of antimicrobial resistance. However, recent studies have shown that cationic antimicrobial peptides are a promising family of antibacterial agents that are active against oral pathogenic bacteria and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 132 publications
(237 reference statements)
0
27
0
Order By: Relevance
“…Many important prospects for the approved AMPs by the US FDA are used in clinical applications, such as ophthalmology, dental, wound healing, and surgical infection ( Izadi et al, 2020 ). Several AMPs have shown tremendous therapeutic potential against various infectious diseases caused by pathogenic bacteria, including peptide ZXR-2 (FKIGGFIKKLWRSLLA) against pathogenic bacteria of dental caries, Porphyromonas gingivalis , Streptococcus sobrinus , Streptococcus mutans , and peptide PAC-113 (Clinical trial identifier: NCT00659971) as effective antimicrobial agents against oral candidiasis ( Chen et al, 2017 ; Sztukowska et al, 2019 ; Lin et al, 2021 ). Also, the results of several AMPs studies including in vivo and clinical trials have indicated the good therapeutic potential in treating various surgical infections and wound healing.…”
Section: Current Progress Of Amps In Medical Applicationsmentioning
confidence: 99%
“…Many important prospects for the approved AMPs by the US FDA are used in clinical applications, such as ophthalmology, dental, wound healing, and surgical infection ( Izadi et al, 2020 ). Several AMPs have shown tremendous therapeutic potential against various infectious diseases caused by pathogenic bacteria, including peptide ZXR-2 (FKIGGFIKKLWRSLLA) against pathogenic bacteria of dental caries, Porphyromonas gingivalis , Streptococcus sobrinus , Streptococcus mutans , and peptide PAC-113 (Clinical trial identifier: NCT00659971) as effective antimicrobial agents against oral candidiasis ( Chen et al, 2017 ; Sztukowska et al, 2019 ; Lin et al, 2021 ). Also, the results of several AMPs studies including in vivo and clinical trials have indicated the good therapeutic potential in treating various surgical infections and wound healing.…”
Section: Current Progress Of Amps In Medical Applicationsmentioning
confidence: 99%
“…Suspensions of multi-species of facultative anaerobic bacteria (FAB) including Actinomyces naeslundii, Streptococcus mutans and Streptococcus sanguinis or obligate anaerobic bacteria (OAB) including Parvimonas micra, Veillonella parvula and Fusobacterium nucleatum were subjected to concentration ranges of LL-37 and LfcinH. Compared to LfcinH, prominent inhibitory threshold concentrations of LL-37 were noticed (p < 0.0001) but the biofilm mass was also decreased better by LL-37 compared to LfcinH, highlighting the scope of LL-37 as a better AMP [168,169].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…[61] This mechanism of action has meant that AMPs do not readily induce resistance and are highly effective against antibiotic-susceptible and multi-drug-resistant bacteria [62] in both nosocomial and uropathogenic pathogens. [63] This attractive characteristic has inspired that the incorporation of AMPs can become a major research focus in preventing or reducing the growth of bacteria and biofilms. [64][65][66][67] Thus, AMPs have emerged as alternatives to routinely used antibiotics and are now being considered a new class of antimicrobial surface coatings.…”
Section: Polymer-based Dental Implantsmentioning
confidence: 99%